2012
DOI: 10.1002/zaac.201200233
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Rich Framework Selenoarsenates Based on Icosahedral Cu8Se13 Clusters

Abstract: Abstract. Three copper-rich framework selenoarsenates, (H 2 en) 1.5 -[Cu 8 (μ 8 -Se)(AsSe 4 ) 6/2 ] (1), (H 2 dap) 1.5 [Cu 8 (μ 8 -Se)(AsSe 4 ) 6/2 ] (2), and Na 2 (H 2 dap) 0.5 [Cu 8 (μ 8 -Se)(AsSe 4 ) 6/2 ] (3), were synthesized under solvothermal conditions. These three compounds are isostructural and contain a 3D Cu-As-Se framework constructed from novel icosahedral Cu 8 Se 13 clusters linked by As 5+ , with counterions located in the cavi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The wide variety of structures and properties of chalcogenidoarsenates have led to great interest in many areas, including semiconductors, photoelectricity, magnetism, ion exchange, and nonlinear optics ( Sheldrick and Wachhold, 1998 ; Zhou et al, 2009 ; Zhang et al, 2012 ; Xiong et al, 2013 ; Yao et al, 2013 ; Liu et al, 2014 ; Zhou et al, 2015 ; Zhou, 2016 ; An et al, 2017 ; Wang et al, 2020 ; Chen et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ). The chalcogenidoarsenates are formed by corner- or edge-sharing of [AsQ 3 ] 3- and [AsQ 4 ] 3- (Q = S, Se) units, resulting in a variety of chalcogenidoarsenate aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide variety of structures and properties of chalcogenidoarsenates have led to great interest in many areas, including semiconductors, photoelectricity, magnetism, ion exchange, and nonlinear optics ( Sheldrick and Wachhold, 1998 ; Zhou et al, 2009 ; Zhang et al, 2012 ; Xiong et al, 2013 ; Yao et al, 2013 ; Liu et al, 2014 ; Zhou et al, 2015 ; Zhou, 2016 ; An et al, 2017 ; Wang et al, 2020 ; Chen et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ). The chalcogenidoarsenates are formed by corner- or edge-sharing of [AsQ 3 ] 3- and [AsQ 4 ] 3- (Q = S, Se) units, resulting in a variety of chalcogenidoarsenate aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The [AgAs 2 Se 5 ] n 3- chains consist of ψ -bitetrahedral [As 2 Se 5 ] 4- units and tetrahedral coordinated Ag + ions ( Wachhold and Kanatzidis, 1999 ). The three-dimensional [Cu 8 ( μ 8 -Se) (AsSe 4 ) 6/2 ] n 3- framework is constructed of icosahedral Cu 8 Se 13 clusters linked by As 5+ , with counterions located in the cavities ( Zhang et al, 2012 ). The [CdAs 2 Se 4 ] n 2- chain synthesized by our group is made up of a tetrahedral [CdSe 4 ] connected to a dimer As 2 4+ through an As-Se bond, whereas the [HgAs 2 Se 4 ] n 2- chain is formed by of a tetrahedral [HgSe 4 ] connected to a dimer As 2 4+ dimer ( Du et al, 2019 ; Teri et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…1, 9 During the past few decades, owing to the diversity of the bonding modes of the chalcogen atoms, the stereochemical effect of the lone electron pairs and the various coordination orientations of As/Sb(III) by sulfur/ selenium atoms, large structural and compositional diversities have been observed for multinary chalcogenides, and therefore a large number of metal chalcogenides compounds have been prepared. Recently, it has been reported that in the combination of the structural units of As x Q y (Q ¼ S, Se) the As III ions tend to adopt the diverse AsQ n (Q ¼ S, Se) (n ¼ 3-6) ligands that can share corners and/or edges with transition metal ions (TM ¼ Ag + , Cu 2+ , Mn 2+ ), 11,[13][14][15][16][17][18][19][20][21][22][23][24] and could form interesting structural various multinary chalcogenides, 8 such as 1D chains, 2D layers, 3D framework. For example, RbAg 2 As 3 Se 6 , 10 NaAg 2 AsS 3 $H 2 O, 13 (NH 3 CH 2 CH 2 NH 3 )AgAsS 4 , 14 CsAgAs 2 Se 4 , 15 27 From the above instances we can see clearly that it is relatively rare for alkali metals cations used as structural directing agents to contain Hg/Cd arsenic chalcogenides in the M-TM-As-Q (M ¼ alkali metals; TM ¼ Hg, Cd; Q ¼ S, Se) systems.…”
Section: Introductionmentioning
confidence: 99%
“…The central Se 2À ion bonded to eight tetrahedrally coordinated Cu + ions has a bond valence sum of 2+, which satisfies Pauling's electrostatic valence rule. Such kind of cluster already existed in the Cu-As-Se and [Fe(NH 3 ) 6 ]Cu 8 Sb 3 S 13 frameworks, 17,19 which is different from a hollow structure with the planar trigonal coordination of Cu + , such as K 4 Cu 8 Ge 3 S 12 , 18 (H 2 en) 2 Cu 8 Sn 3 S 12 , 21 and (trenH 3 )Cu 7 Sn 4 S 12 . 22 In the structure of the Cu 4 Se 6 cluster, Cu + is planar trigonally coordinated with three Se 2À ions.…”
mentioning
confidence: 99%
“…18 An et al reported the first case of copper-rich selenides with the Cu-As-Se framework. 19 A common feature of these compounds is hollowed Cu 8 S 12 or core-stuffed Cu 8 S 13 /Cu 8 Se 13 icosahedral clusters as SBUs (secondary building units). No other type of cluster co-exists in those open frameworks based on the icosahedral cluster.…”
mentioning
confidence: 99%